2015
DOI: 10.1111/jcmm.12624
|View full text |Cite
|
Sign up to set email alerts
|

The secretome of myocardial telocytes modulates the activity of cardiac stem cells

Abstract: Telocytes (TCs) are interstitial cells that are present in numerous organs, including the heart interstitial space and cardiac stem cell niche. TCs are completely different from fibroblasts. TCs release extracellular vesicles that may interact with cardiac stem cells (CSCs) via paracrine effects. Data on the secretory profile of TCs and the bidirectional shuttle vesicular signalling mechanism between TCs and CSCs are scarce. We aimed to characterize and understand the in vitro effect of the TC secretome on CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 93 publications
3
74
1
1
Order By: Relevance
“…Note the presence of other telopods (Tp) C. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) (TEM A, C X2000, B X2500) TCs and this might indicate a mandatory cooperation during the recruitment and differentiation processes TCs may have an important role in helping the differentiation and migration of stem cells as they can deliver signals to stem cells to differentiate Albulescu et al, 2015). In addition, they might play a role in the process of repair or regeneration by increasing the efficiency of collagen fiber and fibroblasts Bei et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Note the presence of other telopods (Tp) C. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) (TEM A, C X2000, B X2500) TCs and this might indicate a mandatory cooperation during the recruitment and differentiation processes TCs may have an important role in helping the differentiation and migration of stem cells as they can deliver signals to stem cells to differentiate Albulescu et al, 2015). In addition, they might play a role in the process of repair or regeneration by increasing the efficiency of collagen fiber and fibroblasts Bei et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Presumably, this support might contribute to tissue homeostasis, regeneration or repair and transmission of intercellular signals . Ultrastructural evidence showed that telocytes were spatially close not only to capillaries, nerve fibres, myocytes, smooth muscle cells and stem cells but also to macrophages, mast cells, eosinophils and lymphocytes . Telocytes might modulate the immunocytes through direct synapse‐like contact or indirect paracrine communication by secreting soluble mediators, such as IL‐6, VEGF and nitric oxide .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural evidence showed that telocytes were spatially close not only to capillaries, nerve fibres, myocytes, smooth muscle cells and stem cells but also to macrophages, mast cells, eosinophils and lymphocytes . Telocytes might modulate the immunocytes through direct synapse‐like contact or indirect paracrine communication by secreting soluble mediators, such as IL‐6, VEGF and nitric oxide . Although telocytes were reported to be involved in multiple autoimmune, inflammatory and fibrotic disorders, their number was decreased and their morphology was disrupted in these conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that TCs can secrete certain cytokines, including VEGF (vascular endothelial growth factor), IL-6 (interleukin-6), MIP-1α (macrophage inflammatory protein 1-α), thus playing a modulatory role in stem cell proliferation and differentiation (Albulescu et al, 2015) or promoting the proliferation and angiogenesis of human pulmonary microvascular endothelial cells . This study showed that the ratio of VSMCs in S and G2/M phase increased when VSMCs were incubated with the supernatant of TCs.…”
Section: The Underlying Mechanisms By Which Tcs Promote the Proliferamentioning
confidence: 99%